Answer:
15.05
Step-by-step explanation:
Also, you don't need to add the zeros, they don't mean anything.
Recall the binomial theorem.
![(a+b)^n = \displaystyle \sum_{k=0}^n \binom nk a^{n-k} b^k](https://tex.z-dn.net/?f=%28a%2Bb%29%5En%20%3D%20%5Cdisplaystyle%20%5Csum_%7Bk%3D0%7D%5En%20%5Cbinom%20nk%20a%5E%7Bn-k%7D%20b%5Ek)
1. The binomial expansion of
is
![\left(1 + \dfrac x3\right)^7 = \displaystyle\sum_{k=0}^7 \binom 7k 1^{7-k} \left(\frac x3\right)^k = \sum_{k=0}^7 \binom 7k \frac{x^k}{3^k}](https://tex.z-dn.net/?f=%5Cleft%281%20%2B%20%5Cdfrac%20x3%5Cright%29%5E7%20%3D%20%5Cdisplaystyle%5Csum_%7Bk%3D0%7D%5E7%20%5Cbinom%207k%201%5E%7B7-k%7D%20%5Cleft%28%5Cfrac%20x3%5Cright%29%5Ek%20%3D%20%5Csum_%7Bk%3D0%7D%5E7%20%5Cbinom%207k%20%5Cfrac%7Bx%5Ek%7D%7B3%5Ek%7D)
Observe that
![k = 1 \implies \dbinom 71 \left(\dfrac x3\right)^1 = \dfrac73 x](https://tex.z-dn.net/?f=k%20%3D%201%20%5Cimplies%20%5Cdbinom%2071%20%5Cleft%28%5Cdfrac%20x3%5Cright%29%5E1%20%3D%20%5Cdfrac73%20x)
![k = 2 \implies \dbinom 72 \left(\dfrac x3\right)^2 = \dfrac73 x^2](https://tex.z-dn.net/?f=k%20%3D%202%20%5Cimplies%20%5Cdbinom%2072%20%5Cleft%28%5Cdfrac%20x3%5Cright%29%5E2%20%3D%20%5Cdfrac73%20x%5E2)
When we multiply these by
,
•
and
combine to make ![\frac{56}3 x^2](https://tex.z-dn.net/?f=%5Cfrac%7B56%7D3%20x%5E2)
•
and
combine to make ![-\frac{63}3 x^2 = -21x^2](https://tex.z-dn.net/?f=-%5Cfrac%7B63%7D3%20x%5E2%20%3D%20-21x%5E2)
and the sum of these terms is
![\dfrac{56}3 x^2 - 21x^2 = \boxed{-\dfrac73 x^2}](https://tex.z-dn.net/?f=%5Cdfrac%7B56%7D3%20x%5E2%20-%2021x%5E2%20%3D%20%5Cboxed%7B-%5Cdfrac73%20x%5E2%7D)
2. The binomial expansion is
![\left(2a - \dfrac b2\right)^8 = \displaystyle \sum_{k=0}^8 \binom 8k (2a)^{8-k} \left(-\frac b2\right)^k = \sum_{k=0}^8 \binom 8k 2^{8-2k} a^{8-k} b^k](https://tex.z-dn.net/?f=%5Cleft%282a%20-%20%5Cdfrac%20b2%5Cright%29%5E8%20%3D%20%5Cdisplaystyle%20%5Csum_%7Bk%3D0%7D%5E8%20%5Cbinom%208k%20%282a%29%5E%7B8-k%7D%20%5Cleft%28-%5Cfrac%20b2%5Cright%29%5Ek%20%3D%20%5Csum_%7Bk%3D0%7D%5E8%20%5Cbinom%208k%202%5E%7B8-2k%7D%20a%5E%7B8-k%7D%20b%5Ek)
We get the
term when
:
![k=2 \implies \dbinom 82 2^{8-2\cdot2} a^{8-2} b^2 = 28 \cdot2^4 a^6 b^2 = \boxed{448} \, a^6b^2](https://tex.z-dn.net/?f=k%3D2%20%5Cimplies%20%5Cdbinom%2082%202%5E%7B8-2%5Ccdot2%7D%20a%5E%7B8-2%7D%20b%5E2%20%3D%2028%20%5Ccdot2%5E4%20a%5E6%20b%5E2%20%3D%20%5Cboxed%7B448%7D%20%5C%2C%20a%5E6b%5E2)
Answer:
quadrant 1
Step-by-step explanation:
quadrant 1 is (-,+)
Answer: There is 3.994% continuous growth rate per hour.
Step-by-step explanation:
Since we have given that
Initial bacteria = 2600
After two and a half hours,
Number of bacteria = 2873
We need to find the continuous growth rate per hour.
As we know the equation for continuous growth rate per hour.
![y=y_0e^{rt}\\\\2873=2600e^{2.5r}\\\\\dfrac{2873}{2600}=e^{2.5r}\\\\1.105=e^{2.5r}\\\\\text{Taking log on both the sides}\\\\\ln 1.105=2.5r\\\\0.0998=2.5r\\\\r=\dfac{0.0998}{2.5}\\\\r=0.0399\times 100\\\\r=3.994\%](https://tex.z-dn.net/?f=y%3Dy_0e%5E%7Brt%7D%5C%5C%5C%5C2873%3D2600e%5E%7B2.5r%7D%5C%5C%5C%5C%5Cdfrac%7B2873%7D%7B2600%7D%3De%5E%7B2.5r%7D%5C%5C%5C%5C1.105%3De%5E%7B2.5r%7D%5C%5C%5C%5C%5Ctext%7BTaking%20log%20on%20both%20the%20sides%7D%5C%5C%5C%5C%5Cln%201.105%3D2.5r%5C%5C%5C%5C0.0998%3D2.5r%5C%5C%5C%5Cr%3D%5Cdfac%7B0.0998%7D%7B2.5%7D%5C%5C%5C%5Cr%3D0.0399%5Ctimes%20100%5C%5C%5C%5Cr%3D3.994%5C%25)
Hence, there is 3.994% continuous growth rate per hour.
Ok, were starting at when the stock increased first which is 12 cents on monday. to find your answer your going to need to add all of the increased cents first; then subtract.
12 + 14 = 26
So we have 26 cents, now we subtract the 56.
26 - 56 = -30
now we have -30. now we find out how far away on the number line it is from 12. your answer would be 42.
now for your answer, (i did all of that for other people who had the same question but different answer)
your answer would be 112 cents (which is option B)